Effects of Two Cover Crops [Arachis Repens (L.) Handro And Desmodium Adscendens (SW.) DC.] on The Density of Arbuscular Mycorrhizal Fungi in Soils Under Industrial Banana Plantations in Côte d’Ivoire - Reine Kosso Boka, Nina; Cherif, Mamadou; Jean-Martial Kassi, Koffi Fernand; Didier Kouame, Konan; Tuo, Seydou; Frederic Kouame, Kra; Georges Elisee Amari, Ler-Nogn Dade; Camara, Brahima; Gilchrist Kouadio, Edouard Yves; Emmanuel Dick, Acka (European Scientific Journal, ESJ, 2022)
This study aims to evaluate the effects of two leguminous plants Arachis repens and Desmodium adscendens, used as cover crops, on the proliferation of arbuscular mycorrhizal (AM) fungal spores in soils under industrial banana plantations. Soil samples were collected at two depths (0-10 cm and 10-20 cm) before, 6 and 12 months after the cover crops installation in a three-treatment Fisher block design. After laboratory analysis of the collected soil samples, the results showed that A. repens strongly contributed to the increase of AM fungal spores. Indeed, before planting this legume, the average number of spores which was 882.50 at 0-10 cm of the soil, increased to 1502.50 and then to 2390.00 in 100 g of soil respectively after 6 and 12 months. At the depth of 10-20 cm, the number of spores was 790.00, 1177.50 and 1270 spores/100 g soil, respectively. Acaulospora, Gigaspora, Glomus and Scutellospora were the main genus obtained among the identified spores. Among them, Glomus and Acaulospora were the most abundant. A. repens could be used as a cover crops for the sustainable management of biological soil fertility.